Arenobufagin suppresses the progression of early-stage hepatocellular carcinoma by inhibiting EpCAM-mediated tumor stemness - Lijuan Deng; Lifang Zou; Chunhong Zhou; Fuqin Yang; Fen Ouyang; Yingru Zhu; Huihui Cao; Min Hu; Xiaoshen Zhang; Junshan Liu (Acta Materia Medica)
Epithelial cell adhesion molecule (EpCAM) is a biomarker for epithelial cell-derived tumors. However, the specific role of EpCAM itself in early-stage hepatocellular carcinoma progression remains unclear, and small molecules targeting EpCAM have not yet been reported. Here, the protein expression profile of EpCAM in tumor-adjacent regions was found to be higher than that in tumor regions, and to be positively associated with the progression of early-stage liver cancer, as well as high frequency of recurrence, cirrhosis, lymph node metastasis, microvascular invasion and cancer stemness, in 68 patients with hepatocellular carcinoma (HCC). In vitro , EpCAM enhanced cancer cell stemness, as reflected by increased abilities of proliferation, self-renewal, migration and invasion, which was counteracted by arenobufagin. Furthermore, arenobufagin inhibited the viability of Hep3B and Huh7 cells with IC 50 values of 36.4 nM and 123.4 nM after 72 h of treatment, respectively. Molecular docking data further indicated that arenobufagin binds EpCAM. Moreover, arenobufagin inhibited early progression of HCC through EpCAM in a zebrafish xenograft tumor model mimicking early-stage hepatocellular carcinoma without blood vessels in vivo . This study supports a tumor-promoting role of EpCAM in early-stage hepatocellular carcinoma by facilitating cancer stemness and suggests that arenobufagin might be promising candidate for EpCAM inhibition.